The Bioprotective Effects of Marigold Tea Polyphenols on Obesity and Oxidative Stress Biomarkers in High-Fat-Sugar Diet-Fed Rats - Bader Alsuwayt; Neelam Iftikhar; Abdullah Ijaz Hussain; Ashfaq Ahmad; Irsa Zafar; Arifa Khanam; Wen-Nee Tan; Lutfun Nahar; Afaf F. Almuqati; Esraa Mohammad Haji; Ali F. Almutairy; Satyajit D. Sarker (Cardiovascular Therapeutics)
Conclusion: The results clearly indicate that a high dosage of MPT showed antiobesity activity which was comparable to the same effects produced by the conventional drug orlistat.